THE ROLE OF PERSONNEL DEVELOPMENT IN FORMING THE STRATEGIC SUSTAINABILITY OF TOURISM ENTERPRISES (INNOVATIVE ECONOMY, 2025)
Okhota V.I., Huhul O.Ya.  THE ROLE OF PERSONNEL DEVELOPMENT IN FORMING THE STRATEGIC SUSTAINABILITY OF TOURISM ENTERPRISESPurpose. The aim of the article is to determine the directions of influence of personnel development on the formation of strategic sustainability of tourism enterprises. Methodology of research. Achieving the goal involved the use of: a review analysis, necessary for a comprehensive study of scientific works devoted to the researched issues; a systematization method, with the help of which a list of areas of personnel development was established that influence the improvement of the formation of strategic sustainability of enterprises in the tourism sector; a comparative analysis, with the help of which the positions of scientists were compared regarding the issues of interdependence of the two components.Findings. The key areas of sustainable development of personnel in tourism sector enterprises are identified, in particular: promoting the formation and improvement of personnel skills, promoting the development of personnel well-being, adaptability and involvement in work. It is proven that these areas contribute to improving the implementation of the goals of strategic sustainability of tourism enterprises. It is determined that such an area as promoting the development of personnel well-being occupies an important place in the formation of strategic development of the tourism sector, which is due to its motivational impact on the activation of employees' efforts to support the development of employer enterprises. It was found that the effective use of the strategic area of promoting the development of personnel well-being is associated with the orientation on the theory of resource conservation, which assumes a direct relationship between labour productivity and the growth of resources invested in personnel development. It is substantiated that the application of the theory of resource conservation is relevant for forecasting intangible and material resources necessary to ensure the growth of personnel sustainability in industry enterprises. It was noted that such an area as promoting the development and improvement of personnel skills is a prerequisite for improving the strategic competitive positions of tourism enterprises, since customer loyalty and satisfaction depend on their formation.Originality. The theoretical support for the composition and characteristics of personnel development directions as elements of forming the strategic stability of tourism enterprises in conditions of uncertainty has been further developed.Practical value of the research results lies in the possibility of using provisions regarding the types and characteristics of personnel development directions that affect the strategic sustainability of tourism enterprises when creating strategic programs for industry entities.Key words: tourism enterprises, strategic sustainability, personnel development, personnel skills, personnel welfare development, labour conservation theory, adaptability, work engagement.
Keywords: tourism enterprises; strategic sustainability; personnel skills; personnel development; personnel welfare development; labour conservation theory; adaptability; work engagement